Quantitative Comparison of Genesis and Pore Structure Characteristics of Siliceous Minerals in Marine Shale With Different TOC Contents–A Case Study on the Shale of Lower Silurian Longmaxi Formation in Sichuan Basin, Southern China - Zhang, Kun; Song, Yan; Jiang, Zhenxue; Xu, Dongsheng; Li, Lintao; Yuan, Xuejiao; Liu, Pei; Han, Fengli; Tang, Liangyi; Wang, Xueying; Zhang, Liwen; Jiang, Jinbo; et al. (Frontiers in Earth Science, 2022)
China has abundant shale gas resources with great exploration potential, and stage progress has been made in this aspect. The sedimentary environment and reservoir characteristics are important aspects of the study on shale gas accumulation. Previous studies have mostly been carried out from a “qualitative” perspective, but not from a “quantitative” one. There is a lack of comparative studies on “marine shales with different TOC contents”. This paper takes the marine shale of the first member of the Longmaxi Formation (Long 1 Fm) in southern Sichuan Basin, Southern China, as the research object. The core samples were taken to carry out analyses (mineral composition analysis, TOC content analysis, porosity analysis) and experiments (carbon dioxide and nitrogen adsorption experiments, high-pressure mercury intrusion, FIB-SEM, and FIB-HIM experiments). The element logging data were collected to conduct the quantitative comparison of genesis and pore structure characteristics of siliceous minerals in marine shale with different TOC contents in this area. The conclusions are as follows: first, a formula is used to calculate and determine whether there is excessive silicon; then the Al-Fe-Mn triangle diagram is used to analyze the genesis of excessive silicon, so as to quantitatively analyze the genesis of siliceous minerals in shale: the siliceous minerals of organic shale (1% < TOC <2%) in the member studied are almost terrigenous detrital genesis; most siliceous minerals in organic-rich shale (TOC >2%) are detrital genesis, and a small part (0–20%) are biogenic. Carbon dioxide and nitrogen adsorption experiments, as well as high-pressure mercury intrusion experiments are adopted to quantitatively characterize the whole-aperture pore structure characteristics. The pore development characteristics of different shale components are analyzed by combing FIB-SEM and FIB-HIM experiments. The organic-bearing shales in the target section of this study area mainly develop clay mineral pores (71%), and are dominated by macro-pores (57.3%) with a low number of pores, irregular-shaped pores, as well as poor storage capacity and connectivity; the organic-rich shales in the target section of this study area mainly develop organic pores (51%), and are dominated by micro-pores (32.1%) and mesopores (54%) that are large in number and elliptical-shaped, with good storage capacity and good connectivity. The results of this study help to improve the understanding of the pore size of marine shales, the origin of siliceous minerals in marine shales, and the pore structure characteristics of marine shales, which are of great theoretical and practical significance for improving the theory of shale gas formation and guiding the selection of shale gas sweet spot.